Valorization of cashew nut agricultural residues from Vichada: biorefinery approach, sustainability analysis, and perspectives (2023)
Environmental problem that needs solutions based on sustainability, efficiency, and productivity. Colombia intends to increase its participation in the cashew nut market by cultivating resistant tree varieties of cashew that were developed for being cultivated in Vichada, a region of Colombia with interesting potential for agriculture. Cashew apple and cashew nut shells are the most important residues generated in cashew nut production and represent about 97% of the fruit weight. Furthermore, the vesicant nature of cashew nut shells and the strong flavor of cashew apples make these residues more complex biomasses than other agricultural residues. The contaminant potential of cashew residues could result in the affectation of water sources and soils. On the other hand, these residues may have commercial value that requires research and development to propose an adequate valorization route. Moreover, there is still a gap in the understanding of the chemical composition of cashew residues due to the complexity of this biomass that nowadays can be addressed with technological advances in analytical techniques.